Advances in the pathogenesis and risk factors of deep vein thrombosis in lower extremity fractures - DENG Xin, SU Yun, FU Yutan, ZHANG Haochun,ZHANG Yongkun, WANG Hongxun (Zhongguo linchuang yanjiu)
Lower extremity fracture is a common clinical condition that significantly affects patients'daily activities and work. These patients are often accompanied by major risk factors for deep vein thrombosis (DVT), such as venous wall injury, slow blood flow, and a hypercoagulable state. As a result, the incidence of DVT is high in this population. If prevention and intervention are not promptly implemented, DVT can lead to thromboembolism, which may travel to the pulmonary artery, resulting in pulmonary embolism and posing a serious threat to the patient's life. Therefore, it is crucial to gain a deeper understanding of the pathogenesis and risk factors of DVT. This review summarizes the mechanisms and risk factors associated with DVT in lower extremity fractures, aiming to provide reference for clinicians in the early identification and management of DVT.